2020
DOI: 10.21203/rs.3.rs-59703/v2
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characterization of the Materials and Techniques of a Birthday Inscribed Lacquer Plaque of the Qing Dynasty

Abstract: In this study, in order to analyze the materials and techniques used for the production of the inscribed plaques, multi-analytical scientific approach, including optical microscopy (OM), scanning electron microscopy with energy dispersive X-ray spectroscopy (SEM-EDS), X-ray diffraction (XRD), micro-attenuated total reflection Fourier transform infrared spectroscopy (μ-ATR-FTIR), and micro-Raman spectroscopy (μ-Raman), were used to explore the materials and techniques utilized to create the “Chun Rong Xuan Mao”… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 11 publications
0
2
0
Order By: Relevance
“…the lacquer ash layer (9 stucco layers and 10 fibres layers; the so-called wan lacquering technique) and (c) the lacquer film pigment layer, mostly consisting of organic materials (lacquer sap from Rhus vernicifera ➔ urushiol, animal gelatin, drying oil and proteinaceous materials) and four layers of inorganic pigments: calcite, carbon black, cinnabar and gold (the so-called Jin Jiao technique, i.e., the technique applied to mix pigments and lacquer and "painting lacquer above the gold technique"). & In a birthday inscribed lacquer plaque (1866 AD), Zheng et al (2020) found a primer lacquer layer made of calcite, cinnabar, minium and Chinese lacquer, followed by a second plaster lacquer layer made of gypsum and Chinese lacquer and a third and last layer made of Chinese lacquer.…”
Section: Cinnabar In Lacquered Objectsmentioning
confidence: 99%
“…the lacquer ash layer (9 stucco layers and 10 fibres layers; the so-called wan lacquering technique) and (c) the lacquer film pigment layer, mostly consisting of organic materials (lacquer sap from Rhus vernicifera ➔ urushiol, animal gelatin, drying oil and proteinaceous materials) and four layers of inorganic pigments: calcite, carbon black, cinnabar and gold (the so-called Jin Jiao technique, i.e., the technique applied to mix pigments and lacquer and "painting lacquer above the gold technique"). & In a birthday inscribed lacquer plaque (1866 AD), Zheng et al (2020) found a primer lacquer layer made of calcite, cinnabar, minium and Chinese lacquer, followed by a second plaster lacquer layer made of gypsum and Chinese lacquer and a third and last layer made of Chinese lacquer.…”
Section: Cinnabar In Lacquered Objectsmentioning
confidence: 99%
“…Although lacquer has a long history in China (Zhai et al, 2021) and some researches have disclosed on the ancient lacquer in other areas in China (Jin et al, 2012;Wei et al, 2011;Jin et al, 2017;Hao et al, 2017;Fu et al, 2020;Zheng et al, 2020;Xiao et al, 2020), there is no specific research dedicated to the lacquer craft of marginal area (e.g., the Ba State in the southwest part of China). Furthermore, the beneficial of GCxGC/MS separation of complex additives in lacquer crafting has not yet been explored in archaeological samples except our previous work on pure modern lacquer film (Okamoto et al, 2018).…”
Section: Introductionmentioning
confidence: 99%